If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=x/6+2
We move all terms to the left:
3-(x/6+2)=0
We get rid of parentheses
-x/6-2+3=0
We multiply all the terms by the denominator
-x-2*6+3*6=0
We add all the numbers together, and all the variables
-1x+6=0
We move all terms containing x to the left, all other terms to the right
-x=-6
x=-6/-1
x=+6
| 27^2=16x^2 | | 1=k4− 2 | | 4^1-3x=64 | | k4− 2=2 | | 3^-x+8x=3^13-6x | | 4x-11+19=3x-6x+78 | | 4^6+4n=4^1+5n | | h4−1=3 | | 7^6-3n=7^-6n-6 | | 5+9x-11x=4x-13 | | 0.1-0.02(x+2)=-0.04(3-x) | | 12y+4=14y-10 | | 12^-3v+2=12^7v-8 | | 54-4v=2v | | 4=2v−2 | | 3/8w-1=2 | | -7+b/3=-5 | | 1.9x-1.7=-1.7 | | f(8)=8(8)-5 | | x-10x+9=36 | | -12+6r=-2(8-2r) | | -2y+y-6=3 | | 6x+11x+10x=180 | | 2(x-2)+8=4x-2(-4+x) | | 5a−7a−5=5 | | 5−x|=4 | | 5x-16=-26 | | 0.7v+2.7=1.3 | | 14=-9x-x² | | 2.5x-0.9=19.1 | | 3(3x+2)+-2x=50 | | -8y+6y-5=-11 |